(untitled) (Revista Contexto & Educação, 2025)
The article aims to examine the ways of being a literacy teacher created by the National Literacy Policy (PNA), which was in force in the country from 2019 to 2023. The theoretical framework emerges from the reflections of Michel Foucault and his commentators on the concepts of governmentality and speech analysis. The empirical material consists of the documents that make up the PNA: the text that establishes the National Literacy Policy; the technical-scientific document of the National Textbook Program; the manual about GraphoGame; the manual Tell Me: Family Literacy Guide and the guide Literacy Practices: Literacy Teacher’s Book. The analysis showed three results. The first is linked to the importance that the PNA gives to the educator. The second is that the role of the educator shifts from one who teaches to one who guides learning, centered on the individual. The third result highlights the strong relationships between literacy, scientific evidence and psychological discourse. Thus, the study allows us to affirm that the PNA constitutes a mechanism that captures and guides the teaching of literacy teachers, positioning them as facilitators of a literacy process regulated by psychological discourse, disregarding other forms of literacy.